In vitro test to confirm diagnosis of allopurinol-induced severe cutaneous adverse reactions - J. Klaewsongkram (2018)
© 2016 British Association of Dermatologists Background: Allopurinol is a frequent cause of severe cutaneous adverse reactions (SCARs), such as drug reaction with eosinophilia and systemic symptoms (DRESS), Stevens–Johnson syndrome (SJS) and toxic epidermal necrolysis (TEN). The reactions can potentially be fatal. As drug rechallenge in patients with a history of drug-induced SCARs is contraindicated, in vitro testing may have a diagnostic role as a confirmation test. Objectives: To study the diagnostic value of interferon (IFN)-γ enzyme-linked immunospot (ELISpot) assay as a confirmatory test in patients with a history of allopurinol-induced SCARs. Methods: Peripheral blood mononuclear cells (PBMCs) from 24 patients with a history of allopurinol-induced SCAR (13 DRESS, 11 SJS/TEN) and 21 control subjects were incubated with allopurinol or oxypurinol in the presence or absence of antiprogrammed death ligand 1 antibody (anti-PD-L1). The numbers of IFN-γ-releasing cells after stimulation in each group were subsequently measured with ELISpot. Results: The numbers of IFN-γ-releasing cells in allopurinol-allergic subjects were significantly higher than in control subjects when stimulating PBMCs with oxypurinol 100 μg mL−1, especially when adding anti-PD-L1 supplementation. According to the receiver operating characteristic curve results, the optimal discriminatory power of IFN-γ ELISpot in confirming diagnosis of allopurinol-induced SCARs can be obtained using 16 spot-forming cells per 106PBMCs as a cut-off value upon oxypurinol/anti-PD-L1 stimulation (79·2% sensitivity and 95·2% specificity). Conclusions: The measurement of oxypurinol/anti-PD-L1-inducing IFN-γ-releasing cells yields a high diagnostic value in distinguishing between allopurinol-allergic and control subjects. This technique is beneficial in confirming diagnosis of allopurinol-induced SCARs in patients whose reaction develops while taking multiple drugs.